Pengaruh E-Services Quality Terhadap E-Loyality Yang Dimediasi Oleh Variabel E- Satisfaction Pada Pengguna Ojek Online Go-jek di Jabodetabek - Henny Armaniah; Wasilatun Nikmah (Prisani Cendekia, 2023)
The purpose of this research is to ascertain how electronic service quality influences customer loyalty and satisfaction, the impact of customer experience on customer loyalty, and to what extent electronic satisfaction mediates electronic services. quality on customer loyalty for Go-Jek users in Jabodetabek. Explanatory research using a quantitative approach is a research methodology. 155 people were included in the sample, and a questionnaire was used to collect information. The research variable is e-service quality (X), the dependent variable is customer loyalty (Y), and the mediating variable is e-satisfaction (Z). The results of this study indicate that there is a direct influence between e-service quality (X) on customer loyalty (Y) and e-service quality (X) also has a direct effect on e-satisfaction (Z) for Go-Jek services in Jabodetabek. In addition, e-satisfaction (Z) is able to mediate the effect of e-service quality (X) on customer loyalty (Y).